Relationship Between the Number of Occlusal Supporting and Medical Cost: Analysis Using Large Claims Database from Employee Health Care Insurance in Japan - Tatsunori Murata; Korenori Arai; Kosuke Kashiwagi; Shunsuke Baba (Journal of Health Economics and Outcomes Research, 2020)
# Background There are several previous reports suggesting that the number of remaining teeth is related to increase of total medical expenditure. However, the measurements of oral healthcare conditions used in the previous studies were the number of remaining teeth, and occlusal support was not assessed.